Perancangan Sistem Informasi Geografis Warga Binaan Sosial (WBS) pada Panti Sosial Bina Karya Wanita dengan Menggunakan ARCGIS - Victor Tejaya; Ery Dewayani; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
This social home keeps records of the data manually, the system is not computerized, and the social home has no map for WBS distribution purposes and where the WBS works, so this social home needs a web-based information system that will directly be citizens of the WBS Social Insiders) Who have been in the outside environment of the social home, and make reports on WBS developments, such as their behavior, and what work they have done. The methodology used to create this application is SDLC (System Development Life Cycle). Supporting software used in the design of this system is PHP, HTML, and Mysql that exist in PhpMyAdmin, and also use Arcgis to display maps of WBS locations based on their respective coordinate points..